Evaluation Study of Telephone Counselling Service in the Early Postpartum: To Keep Go on Relationship - ISHII, Misato (Journal of Japan Academy of Midwifery, 2000)
The purpose of this study was to clarify the effects of several telephone counselling ser-vice for primipara in the early postpartum period. The framework of this study was based on the model of Reva Rubin, in the early postpartum, “ Taking in phase”. For experimental group, two of more telephone were made as an intervation between dis-charge and one month. To distinguish the effect of intervention, questionnaire was made at 2 points, [state of primipara in the early postpartum] and [evaluation of medical staff's care]. The [state of primipara in the early postpartum] questionnaire consisted of three categories; Changing physical condition; Daily rhythm; Self Esteem, and [Evaluation of Medical Staff's care] consisted of two sub-categories; Telling about herself ; getting the knowledge and guarantee, and examined the reliability and validity. Subjects are recruited by conbenience and 41 primipara were in expeimental group and 42 were control one. There is not quite differences between two groups. In terms of ‘having a time for herself’ in “daily rhythm” and ‘sense of physical recovrey’ in “changing physical condition”, the point of experimental group was higher than that of control group, at a 0.05 significant level. In addition, telephone counselling servise was approved “telling about herself” in [evaluation of medical staff's care].